Baptisan sebagai Penghapusan Hierarki: Kajian Eksegetis-Teologis atas Galatia 3:26-29 dan Tawaran Ulang Identitas Eklesial di tengah Masyarakat Majemuk - Valeria Sonata; Syani B. Rante Salu; Asih Rachmani Endang Sumiwi (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2026)
This article examines Galatians 3:26–29 as a performative baptismal formula that functions to restructure the social identity of the early Christian community. Employing a grammatical-historical exegesis of the Greek text (NA28) alongside a socio-rhetorical analysis of the Galatian crisis, this study finds that the metaphor of "putting on Christ" (enedusasthe) and the 'oude-oude-kai' conjunctive pattern in verse 28 point back to Genesis 1:27 LXX, thereby indicating a restoration of the created order that abolishes ethnic, class, and gender stratification. The article further traces the tension between the "eschatological indicative" of spiritual equality and Paul's seemingly varied social practice in 1 Corinthians 11, Philemon, and the household codes, proposing a model of progressive realization. These findings are then contextualized within Indonesia's pluralistic society, and the concept of baptismal anamnesis is proposed as a theological foundation for dismantling ecclesial and social hierarchies. Abstrak Artikel ini mengkaji Galatia 3:26-29 sebagai formula baptismal yang bersifat performatif dan berfungsi untuk merestrukturisasi identitas sosial jemaat mula-mula. Dengan menggunakan metode eksegesis gramatikal-historis atas teks Yunani (NA28) dan analisis sosio-retoris terhadap krisis Galatia, penelitian ini menemukan bahwa metafora (enedusasthe) dan pola konjungsi 'oude-oude-kai' pada ayat 28 merujuk kembali pada Kejadian 1:27 LXX, sehingga mengindikasikan pemulihan tatanan penciptaan yang menghapus stratifikasi etnis, kelas, dan gender. Artikel ini juga menelusuri ketegangan antara indikatif eskatologis kesetaraan spiritual dan praktik sosial Paulus yang tampak beragam dalam 1 Korintus 11, Filemon, dan kode rumah tangga, serta mengusulkan model realisasi yang progresif. Temuan ini kemudian direfleksikan secara kontekstual dalam masyarakat Indonesia yang majemuk, dengan mengusulkan konsep anamnesis baptismal sebagai dasar teologis bagi penghapusan hierarki eklesial dan hierarki sosial.